(untitled) (Baltic Journal of Sport and Health Sciences, 2018)
Background. It is stated that the anxiety issue of adolescent pupils has been increasing a concern in teachers and society (Lee & Hankin, 2009; Mocus, Schoot, Klimstra, & Branje, 2011). The analysis of the reasons affecting a poor emotional state, anxiety processes and low self- esteem of adolescents leads to the following factors: socio-economic status, parenting styles (Cohen, Mansoor, Gagin, & Lorber, 2008), insecure attachment and non-functional beliefs (Lee & Hankin, 2009), adaptation difficulties, relationship with peers (Mocus et al., 2011), emotional pressures at school (Klizas, Ramanauskienė, Dumčienė, & Linonis, 2010). Meanwhile, it was found that involvement in sports activities positively affects adolescents’ self-esteem, contributes to adolescents’ identity and positive self- evaluation development, encourages cooperation with peers, develops physical skills, character, creativity, and value system, distracts from harmful habits, and helps to integrate into society (Dunn, Dunn, & Bayduza, 2008; Šniras & Malinauskas, 2006). Thus, it is evident that today’s adolescents, facing growing demands in environment, society, experience more anxiety, which may affect their self-evaluation, self-confidence, self-esteem and vice versa, deteriorate their quality of life and mental health. So, it is highly important for educators (school teachers, coaches, etc.) to understand what causes anxiety in adolescents and how such factors as sport may have an influence on it. Research aim was to determine the relationship between the self-esteem, self-confidence and anxiety for adolescent athletes and non-athletes. Research object was the relationship of adolescents’ self-esteem, self-confidence and anxiety. Methods. The pilot survey was carried out in Kaunas, in 2013. Adolescent athletes and non-athletes aged 16 were selected for the research. The study employed questionnaires survey method. Results and conclusions. It was discovered that the self-esteem and self-confidence of athlete adolescents was higher compared with non-athlete adolescents. The results showed that comparing the different anxiety factors of athlete and non-athlete adolescents no significant differences were found with the exception of anxiety related to social stress experience, and it is lower for athlete respondents. The analysis of self-esteem, self-confidence and anxiety relationship, depending on the sport activity, determined that the sport element had little relevance to these factors. Keywords: students, self-determination, anxiety, sport.